Традиційні метрологічні знання жителів північно-східної частини Чернігівщини - Васянович, О.О. (Сіверщина в історії України, 2021)
У статті за польовими матеріалами, зібраними у Семенівському та Новгород-Сіверському районах Чернігівської області,
розглянуто одиниці вимірювання довжини, площі, часу, ваги та
об’єму. За відсутності годинника вдень слідкували за положенням
сонця над небосхилом, вимірювали довжину тіні, вночі орієнтувалися за співом півнів. Для визначення довжини, крім метрів, послуговувалися антропологічними мірами, що, відповідно до фізичних
властивостей людини, не є сталими одиницями. У досліджуваних
районах значне поширення і застосування мають пристрої для
зважування – кантирі. За відсутності вагів сипучі продукти вимірювали дерев’яними посудинами різної величини, тобто визначали кількість через об’єм. Для вимірювання кількості рідини використовували відро, пляшки різної місткості. Попри уніфікацію
метричних одиниць державою, жителі північно-східної частини
Чернігівщини в домашніх умовах продовжували послуговуватися
досить умовними одиницями вимірювання. Folk knowledge is the result of a long process of cultural adaptation
of man to the environment. Significant interest in traditional folk
knowledge today is due to the applied focus of this branch of folk culture,
the wide range of applications of its centuries-old experience in
modern conditions. Information on folk metrology, which consists of
units of length, area, time, weight, and volume, was formed long ago.
In all ethnic groups, these measures are of folk origin, but upon a state
establishing begins the process of their unification. The article considers
the units of length, area, time, weight, and volume based on field
materials collected in Semenivskyi and Novhorod-Siverskyi districts of
Chernihiv region. In the absence of a clock, the position of the sun over
the sky was monitored during the day, the length of the shadow was
measured, and cock crowing served as guidance at night. To determine
the length, in addition to meters, anthropological measures were used,
which according to the physical properties of man are not fixed units.
To measure a field’s area in Soviet times they used a special ‘sazhenfor-
mowing’, which corresponded to two meters and consisted of two
sticks fastened crosswise in the form of the letter A. Devices for weighing
– ‘cantyr’ – are widespread and used in the study areas. The offi-
cial measure of 1 kilogram is used for weighing, but they also remember
other units of weight: ‘khunt’, ‘pud’, centner, ton, which allows to compare
diff erent units of weight. In the absence of scales, bulk products
were measured with wooden utensils of diff erent sizes or bags, i.e. the
quantity was determined by volume. Conventional units of measure for
grain were special stacks, which were gathered after harvesting. Buckets
and bottles of various capacities were used to measure the amount
of liquid. Despite the unification of metric units by the state, the inhabitants
of the north-eastern Chernihiv region continued to use at home
quite conventional units of measurement, which led to discrepancies in
the measurements of the same values.